Enterprise Architecture Design for Islamic Boarding School Cooperative Transaction Management System: Technology Solutions to Improve Efficiency and Security Transaction - Sudin Saepudin; Dian Amelia Rahman (International Journal of Health Engineering and Technology, 2025)
The development of information technology has had a significant impact on various aspects of life, including in the management of cooperatives, the existence of a transaction management system is also crucial in ensuring efficiency and security in every transaction made. This study aims to design an Enterprise Architecture System for a transaction management system for Islamic boarding school cooperatives, with a focus on increasing efficiency and security in every transaction that occurs. Through an approach using the TOGAF ADM (Architecture Development Method) Model, this study will produce a structured and detailed blueprint, which can be a guide in the implementation of a transaction management system. The successful implementation of this system is expected to improve the quality of service and user satisfaction in Islamic boarding school cooperatives. By facilitating transactions efficiently, providing clarity in every transaction, and improving data security, this platform is expected to provide a better experience for users of Islamic boarding school cooperatives